EVALUATION OF ANTIOXIDANT PROPERTIES AND SENSORY CHARACTERISTICS OF Rhizophora mucronata LEAF TEA INFUSION - Wendy Alexander Tanod; Didit Kustantio Dewanto; Novalina Maya Sari Ansar; Eko Cahyono; Frets Jonas Rieuwpassa; Yana Sambeka (Jurnal Perikanan Unram, 2024)
Rhizophora mucronata leaves are known to have antioxidant properties, including the presence of flavonoids and phenolic compounds. The infusion of these mangrove leaves has the potential for development into herbal drinks. This study aims to evaluate the antioxidant potential of R. mucronata leaves tea infusion that has been dried using sunlight and an oven. The process involved cleaning the R. mucronata mangrove leaves, drying them (either in the sun or in an oven), and grinding them into a powder. This mangrove leaf powder was then brewed with hot water and subsequently dried. The antioxidant capacity of the leaves tea infusion extract was assessed using the DPPH method. Additionally, the sensory acceptance of the mangrove leaves tea infusion was evaluated based on its appearance (color) and aroma. The results demostrated that the percentage inhibition of the mangrove leaves tea infusion extract dried in the sun ranged from 2.80% to 68.83%, with an IC50 of 79.99 ± 0.21 µg/mL. Conversely, the percentage inhibition of the oven-dried mangrove leaves tea infusion extract ranged from 19.25% to 95.41%, with an IC50 of 51.55 ± 0.12 µg/mL. Panelists expressed a moderate appreciation for the appearance (color) and aroma of the R. mucronata leaves tea infusion. No significant differences were observed in the assessments of appearance and aroma between the oven-dried and sun-dried samples. Overall, the findings suggest that R. mucronata leaves possess the potential to be developed into antioxidant-rich herbal drinks that can be appealing to consumers.